Roles of Glu 349 and Asp 352 in membrane insertion and translocation by diphtheria toxin. - Kaul, P. (Cold Spring Harbor Laboratory Press, 1996)
Acidic conditions within the endosomal lumen induce the T domain of receptor-bound diphtheria toxin (DT) to insert into the endosomal membrane and mediate translocation of the toxin's catalytic domain to the cytosol. A conformational rearrangement in the toxin occurring near pH5 allows a buried apolar helical hairpin of the native T domain (helices TH8 and TH9) to undergo membrane insertion. If the inserted hairpin spans the bilayer, as hypothesized, then the two acidic residues within the TL5 interhelical loop, Glu 349 and Asp 352, should become exposed at the neutral cytosolic face of the membrane and reionize. To investigate the roles of these residues in toxin action, we characterized mutant toxins in which one or both acidic residues had been replaced with nonionizable ones. Each of two double mutants examined showed a several-fold reduction in cytotoxicity in 24-h Vero cell assays (sixfold for E349A + D352A and fourfold for E349Q + D352N), whereas the individual E349Q and D352N mutations caused smaller reductions in toxicity. The single and double mutations also attenuated the toxin's ability to permeabilize Vero cells to Rb+ at low pH and decreased channel formation by the toxin in artificial planar bilayers. Neither of the double mutations affected the pH-dependence profile of the toxin's conformational rearrangement in solution, as measured by binding of the hydrophobic fluorophore, 2-p-toluidinyl-naphthalene 6-sulfonate. The results demonstrate that, although there is no absolute requirement for an acidic residue within the TL5 loop for toxicity, Glu 349 and Asp 352 do significantly enhance the biological activity of the protein. The data are consistent with a model in which ionization of these residues at the cytosolic face of the endosomal membrane stabilizes the TH8/TH9 hairpin in a transmembrane configuration, thereby facilitating channel formation and translocation of the toxin's catalytic chain.